The Political Economy of Early Covid-19 Interventions in US States - Martín Gonzalez-Eiras; Dirk Niepelt (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate how politico-economic factors shaped government responses to the spread of COVID-19. Our simple framework uses epidemiological, economic and politico-economic arguments. Confronting the theory with US state level data we find strong evidence for partisanship even when we control for fundamentals including the electorate's political views. Moreover, we detect an important role for the proximity of elections which we interpret as indicative of career concerns. Finally, we find suggestive evidence for complementarities between voluntary activity reductions and government imposed restrictions.
Keywords: I18; 330; Covid-19; lockdown; politics